Data Journalism beyond Majority World Countries: Challenges and Opportunities. Issue 9 (21st October 2019) - Wright, Kate; Zamith, Rodrigo; Bebawi, Saba
ABSTRACT: This commentary reflects on the state of research on data journalism and discusses future directions for this line of work. Drawing on theory in international development and postcolonial studies, we discuss three critical pitfalls that we encourage future scholarship in this area to avoid. These include using a linear model of progress, in which journalists in Majority World nations struggle to 'catch up' to their Minority World counterparts because of the 'obstacles' they face; reproducing a simplistic split between the 'West and the Rest', thus missing the complex interaction of structures operating at different levels; and failing to examine journalistic agency due to an overemphasis on the technical structuring of the 'tools' used in data journalism. We also encourage scholars to engage in more comparative work rather than single case studies; increase dialogic communication between scholarship produced in, or about, different parts of the world; and incorporate more diverse methodologies with the aim of building theory. More broadly, we advocate for greater critical reflection upon—if not the challenging of—our dominant modes of thought in order to build more nuanced frameworks for explaining the complex causes, and potentially mixed effects, of data journalism around the world.